Patient satisfaction with nursing care : a meta synthesis - Chawani, Felesia Samuel (2009)
M.Sc. (Nursing), Faculty of Health Sciences, University of the Witwatersrand, 2009 The purpose of this study is to undertake an interpretive, descriptive meta synthesis of available literature of primary qualitative research findings on patient satisfaction with nursing care of adult patients in hospitals across the world. The study addresses the question about the experiences and expectations of adult patients regarding nursing care. It is argued that patient satisfaction provides a meaningful focus for improving quality of care, planning and evaluation of health care services. The data collected in this study were from the identified articles from a range of databases including Science direct, PubMed, CINAHL and EBSCO host. The findings reveal that 13 studies met the inclusion criteria. Four of these were undertaken in the Sweden, two in the USA, two in the UK, and one each from China, Iceland, Ireland, Greece and Western Australia. The population study sampled was 341 adult patients in the included primary research reports. The total population comprises of 132 males and 166 females. In the literature 49 themes were derived which were synthesised to four new themes namely: Caring, quality of care, communication and information, professional technical skills and competence, organizational and environmental factors. Therefore, this study focuses on these five themes that contribute to patient satisfaction. In conclusion, this study points out that despite the dissatisfaction with nursing care, some satisfaction were experienced and that these should be used for those considering whether or not to use patient satisfaction views and opinions in the care.